STRATEGI PEMASARAN PARIWISATA TERPADU: MENINGKATKAN BRAND IMAGE PULAU SEMAU, NUSA TENGGARA TIMUR MELALUI FESTIVAL LI NGAE - I Putu Budiarta; A. Agung Putu Swabawa; I Ketut Suja; Solihin Mulyadi; I Wayan Basi Arjana (Sekolah Tinggi Pariwisata Mataram, 2023)
This study aims to determine the integrated marketing strategy in building the brand image of Semau Island through the Li Ngae festival. This is a qualitative research using the case study method. The theory used in this study is integrated marketing communications with several concepts such as product, price, place, promotion, people, process, and physical evidence used by researcher in analyzing the role of the regional government in creating the brand image of Semau Island. Data collection technique is done by interview and documentation. The results show that the integrated marketing communication strategy in creating the brand image of Semau Island is through the Li Ngae festival by developing infrastructure and facilities in the tourist areas of Otan and Liman Beach especially in 3 A (accessibility, amenities, and atraction). Accessibility is facility and infrastructure to tourist destinations, road access, and means of transportation and road signs. Amenities is all supporting facilities that meet the needs of tourists in the form of accommodation, restaurants and other facilities such as toilets and parking lots. Attractions are the main product of a tourist destination that can be enjoyed by tourists. It is a slooping and a small wave of Otan Beach, and Liman beach which has clean and white sand, Liman hill where visitors can see to all direction which give a sensation and extraordinary natural beauty. Tourism promotion is done through printed and electronic media and internet. Key words: Marketing strategy, brand image, Li Ngae festival.